Proteomic and genomic studies of non-alcoholic fatty liver disease - clues in the pathogenesis - Lim, Jun Wei (Baishideng Publishing Group Inc, 2014)
Non-alcoholic fatty liver disease (NAFLD) is a widely prevalent hepatic disorder that covers wide spectrum of liver pathology. NAFLD is strongly associated with liver inflammation, metabolic hyperlipidaemia and insulin resistance. Frequently, NAFLD has been considered as the hepatic manifestation of metabolic syndrome. The pathophysiology of NAFLD has not been fully elucidated. Some patients can remain in the stage of simple steatosis, which generally is a benign condition; whereas others can develop liver inflammation and progress into non-alcoholic steatohepatitis, fibrosis, cirrhosis and hepatocellular carcinoma. The mechanism behind the progression is still not fully understood. Much ongoing proteomic researches have focused on discovering the unbiased circulating biochemical markers to allow early detection and treatment of NAFLD. Comprehensive genomic studies have also begun to provide new insights into the gene polymorphism to understand patient-disease variations. Therefore, NAFLD is considered a complex and mutifactorial disease phenotype resulting from environmental exposures acting on a susceptible polygenic background. This paper reviewed the current status of proteomic and genomic studies that have contributed to the understanding of NAFLD pathogenesis. For proteomics section, this review highlighted functional proteins that involved in: (1) transportation; (2) metabolic pathway; (3) acute phase reaction; (4) anti-inflammatory; (5) extracellular matrix; and (6) immune system. In the genomic studies, this review will discuss genes which involved in: (1) lipolysis; (2) adipokines; and (3) cytokines production.